Meta-Analysis of the Effects of Diet and Physical Activity on HbA1c in Type II Diabetes Mellitus Patients - Kusumaningrum, Utari; Murti, Bhisma; Prasetya, Hanung (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Type II Diabetes Mellitus is still a global health problem. The prevalence of diabetes has increased over the decades due to the increased incidence of Type II DM. This study aims to analyze the effectiveness of diet therapy and physical activity on HbA1c levels in type II DM patients.Subject and Method: This study is a systematic and meta-analysis study, with the following PICO Population = Patients diagnosed with type II DM. Intervention= High physical activity and diet therapy. Comparison = Low physical activity and no diet. Outcome= HbA1c level. The articles used in this study were obtained from several databases, including PubMed, Science Direct, Scopus, Clinical Key, and Google Scholar. The keywords used were: “tertiary prevention and DM”, “diet”, “physical activity”, “diet and DM” “physical activity and DM”, “diet and tertiary prevention and DM”. The inclusion criteria were full-text articles, experimental study design using randomized controlled trial (RCT). Articles were collected using PRISMA flow diagram. Articles were analyzed using Review Manager 5.3 application.Results: A meta-analysis of 9 articles on the effectiveness of diet therapy on HbA1c levels from Spain, the United States, Japan, the United Kingdom, and Israel concluded that Type II DM patients on diet therapy had an HbA1c level of 0.49 units compared to Type II DM patients without treatment, and the results were statistically significant (SMD= -0.49; 95% CI= -0.56 to -0.42; p < 0.001). A meta-analysis of 9 articles on the effectiveness of physical activity on HbA1c levels from the United States, Australia, Italy, and India concluded that Type II DM patients with high physical activity had HbA1c levels by 0.81 units lower than Type II DM patients with low physical activity, and the results were statistically significant (SMD= -0.81; 95% CI= -1.20 to -0.43; p < 0.001).Conclusion: Diet therapy and high physical activity reduce HbA1c levels in type II DM patients.Keywords: Physical activity, diet, HbA1c, type II DMCorrespondence: Utari Kusumaningrum. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: utariikusuma@gmail.com. Mobile: +6289636061501.Indonesian Journal of Medicine (2022), 07(02): 172-187https://doi.org/10.26911/theijmed.2022.07.02.06